Identifying cleaning products associated with short-term work-related respiratory symptoms: A workforce-based study in domestic cleaners. (April 2022) - De Troeyer, Katrien; De Man, Jeroen; Vandebroek, Eline; Vanoirbeek, Jeroen A; Hoet, Peter HM; Nemery, Benoit; Vanroelen, Christophe; Casas, Lidia; Ronsmans, Steven
Graphical abstract: Abstract: Domestic cleaners have an increased risk of asthma-like and other respiratory symptoms and conditions. Uncertainty exists about which products are most hazardous. We aimed to investigate, among professional domestic cleaners, the associations of ocular/respiratory outcomes with using specific types of products at work and with the ability to choose their own products. Among domestic cleaners employed by "service vouchers" companies in Belgium, we administered an online questionnaire on ocular/respiratory symptoms (frequency and time relation to workdays), frequency of use of 40 types of products, and ability to choose one's own products. Work-relatedness was defined as symptoms improving/disappearing on days off-work. We studied associations between frequency of product-use with work-related outcomes (eye irritation, rhinitis symptoms, sore throat, laryngeal symptoms, asthma symptoms, cough) and with chronic bronchitis, using multivariable logistic and elastic net regression. Adjusted odds ratios (OR) with 95%-confidence intervals were obtained per time a product was used per week. Among 1, 586 domestic cleaners (99% women), the number of times sprays were used (median 13/week) was significantly associated with all outcomes (ORs between 1.012 and 1.024 per time sprays were used per week). Bleach/disinfectant-containing liquid products were associated with all outcomes, except for laryngeal symptoms (ORs 1.086 to 1.150); ammonia with work-related upper airway symptoms and chronic bronchitis. Cleaners able to choose their own products had fewer work-related eye symptoms (OR 0.728;0.556–0.954), rhinitis (OR 0.735;0.571–0.946) and cough (OR 0.671;0.520–0.865). Using elastic net regression, work-related rhinitis was most strongly associated with mould removal spray (OR 1.108;1.006–1.248), carpet/seat/curtain spray (OR 1.099;1.001–1.304) and ammonia (OR 1.081;1.002–1.372); work-related asthma with carpet/seat/curtain spray (OR 1.103;1.017–1.322), mould removal spray (OR 1.029;0.995–1.199) and drain cleaner (OR 1.023;0.979–1.302). In a large group of domestic cleaners, we documented that cleaning products have a range of adverse respiratory effects. Empowering cleaners to choose their products may reduce the burden of symptoms.